2012
DOI: 10.1186/1471-2407-12-480
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a promotes ewing sarcoma cell migration through upregulating CXCR4 expression

Abstract: BackgroundAs one of the malignant tumors most often affecting children and young adults, Ewing sarcoma (ES) is characterized by early metastasis contributing to unfavorable prognosis. However, the molecular mechanisms responsible for ES metastasis remain poorly understood. In this study, we aimed to explore whether Wnt5a, a putative pro-metastatic factor, plays a role in ES metastasis.MethodsExpression of Wnt5a and CXCR4 was determined by real-time PCR or Western blot in 15 ES specimens and 4 ES cell lines, A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…The increase in JUN mRNA levels was reflected by an increase in JUN protein levels. These data are consistent with studies showing that knock-down of WNT5A decreased phospho-JUN levels in a sarcoma cell line (Jin et al, 2012) and that WNT5A upregulated phospho-JUN levels in NIH3T3 fibroblasts (Nomachi et al, 2008). Pharmacological inhibition of MAPK8 or Rac1 blocked the ability of WNT5A to stimulate phosphorylation of JUN and expression of JUN and FOS (present study).…”
Section: Discussionsupporting
confidence: 93%
“…The increase in JUN mRNA levels was reflected by an increase in JUN protein levels. These data are consistent with studies showing that knock-down of WNT5A decreased phospho-JUN levels in a sarcoma cell line (Jin et al, 2012) and that WNT5A upregulated phospho-JUN levels in NIH3T3 fibroblasts (Nomachi et al, 2008). Pharmacological inhibition of MAPK8 or Rac1 blocked the ability of WNT5A to stimulate phosphorylation of JUN and expression of JUN and FOS (present study).…”
Section: Discussionsupporting
confidence: 93%
“…Studies of Ewing sarcoma tumors and cell lines have previously identified a potential role for the CXCR4/SDF-1α axis in Ewing sarcoma pathogenesis [4, 16, 28, 29]. In particular, interrogation of gene expression databases identified an association between high levels of the CXCR4 transcript and metastatic disease [4].…”
Section: Discussionmentioning
confidence: 99%
“…35 Many studies have reported that Wnt5a can increase the metastasis of osteosarcoma. [5][6][7][8][9][10] One study showed that Wnt5a can promote breast cancer cell migration via the Dvl2/Rab35/Rac1 signaling pathway. 36 In this study, we found that increased LDOC1 expression in osteosarcoma cells specifically decreases Wnt5a, but not Dvl2, levels.…”
Section: Discussionmentioning
confidence: 99%
“…2 The Wnt5a signaling pathway is involved in metastasis regulation in many tumor types, including osteosarcoma. [5][6][7][8][9][10] The LDOC1 (leucine zipper, down-regulated in cancer 1) protein has been shown to localize to the nucleus, and its expression is down-regulated in pancreatic and gastric cancer cells, compared to the corresponding normal human tissue. 11,12 These observations led to the hypothesis that LDOC1 functions as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%